A 7.5 MHz Dual-Layer Transducer Array for 3-D Rectilinear Imaging - Chen, Yuling (2011)
The difficulties associated with fabrication and interconnection have limited the development of 2-D ultrasound transducer arrays with a large number of elements (>5000). In previous work, we described a 5 MHz center frequency PZT-P[VDF-TrFE] dual-layer transducer, which used 2 perpendicular 1-D arrays for 3-D rectilinear imaging. This design substantially reduces the channel count as well as fabrication complexity, which makes 3-D imaging more realizable. Higher frequencies (>5MHz) are more commonly used in clinical for imaging targets near transducers such as the breast, carotid, and musculoskeletal. In this paper, we present a 7.5 MHz dual-layer transducer array for 3-D rectilinear imaging. A modified acoustic stack model was designed and fabricated. PZT elements were sub-diced to eliminate lateral coupling. This sub-dicing process made the PZT into a 2–2 composite material, which could help improve transducer sensitivity and bandwidth. Full synthetic aperture 3-D data sets were acquired by interfacing the transducer with a Verasonics data acquisition system (VDAS). Offline 3-D beamforming was then performed to obtain volumes of a multi-wire phantom and a cyst phantom. The generalized coherence factor (GCF) was applied to improve the contrast of cyst images. The measured −6 dB fractional bandwidth of the transducer was 71% with a center frequency of 7.5 MHz. The measured lateral beamwidths were 0.521 mm and 0.482 mm in azimuth and elevation respectively, compared with a simulated beamwidth of 0.43 mm.